Human vitreous concentrations of citicoline following topical application of citicoline 2% ophthalmic solution - Carnevale, Carmela; Manni, Gianluca; Roberti, Gloria; Micera, Alessandra; Bruno, Luca; Cacciamani, Andrea; Altafini, Romeo; Quaranta, Luciano; Agnifili, Luca; Tanga, Lucia; Riva, Ivano; Oddone, Francesco (PloS one, 2019)
To evaluate the presence and concentration of citicoline and its metabolites (choline, cytidine and uridine) in the vitreous body in human eyes after topical application of an ophthalmic solution of citicoline 2%, in vivo. Twenty-one subjects affected by epiretinal membrane with surgical indication for pars-plana vitrectomy underwent treatment with 1 drop 3 times/day of a solution of citicoline 2%, 0.2% high molecular weight hyaluronic acid and 0.01% benzalkonium chloride (OMK1, Omikron Italia s.r.l., Rome, Italy) 14 days before surgery and 2 hours prior to surgery. Five additional patients served as controls and received an OMK1 vehicle solution without citicoline. The vitreous samples were taken at the beginning of the pars-plana vitrectomy and analyzed for qualitative/quantitative determination of vitreous concentration of citicoline and its metabolites by means of high performance liquid chromatography. The overall mean concentration of citicoline in patients treated with citicoline 2% solution was 406.72 ± 52.99 μg/mL, while the mean concentration of choline, cytidine and uridine was 180.88 ± 41.49 μg/mL, 44.45 ± 10.19 μg/mL and 330.41 ± 75.8 μg/mL, respectively. The concentration of citicoline in phakic eyes (n = 13, 366.61 ± 129.61 μg/mL) was lower compared to that found in pseudophakic eyes (n = 8, 435.89 ± 131.42 μg/mL) and the difference was not statistically significant. The concentration of citicoline in the control eyes was 45.66 ± 26.36 μg/mL, while the concentration of choline, cytidine and uridine were 17.21 ± 9.93 μg/mL, 6.24 ± 3.6 μg/mL and 172.80 ± 99.76 μg/mL, respectively. Citicoline can reach the human vitreous in high concentration when administered in ophthalmic solution. This evidence contributes to the build-up of the pyramid of the evidences required for determining the role of citicoline administered in ophthalmic formulation in retinal and optic nerve neurodegenerative diseases.